Comparison of the Antibacterial Effect of Different Biological Silver Nanoparticles Synthetized and Integrated with Honeys - Clebis, Victor Hugo; Scandorieiro, Sara; Spinosa, Wilma Aparecida; da Costa, Viviane Lopes Leite; Lourenço, Isabella Martins; Seabra, Amedea Barozzi; Kobayashi, Renata Katsuko Takayama; Nakazato, Gerson (New Environmentally-Friendly Materials, 2022)
This study compares the morphologies, zeta potentials, and antibacterial effects a total 12 different microcompounds containing honey and silver nanoparticles, in a novel study of the difference between honey samples in nanoparticle synthesis, as well as the antibacterial interaction that those honey samples can have with the silver nanoparticles synthetized using them. Microcompounds were synthetized by combining silver nitrate solution with a honey sample and performing one of methods of biogenic synthesis: sunlight exposure, basification to pH 5 or basification to pH 10. Samples of each microcompound were also submitted to heat treatment, obtaining thus heated variants. Morphology and size data were obtained by Dynamic Light Scattering (DLS) analysis and Scanning Electron Microscopy (SEM); while zeta potential was measured by Electrophoretic Light Scattering. Broth microdilution, time-kill curves and SEM were used to access the antibacterial effect. Mean diameter of particles inside all microcompounds varied between 100 nm and 150 nm; and the zeta potential varied depending on the honey used. Minimal Inhibitory Concentrations (MIC) of microcompounds were between 15 μM and 500 μM. Time-kill curves showed that microcompounds had a faster and stronger effect against Escherichia coli than Staphylococcus aureus. Microcompounds obtained by basification to pH 5 or by sunlight were bactericidal, as they were capable of inhibiting bacterial growth (resulting in an antibacterial efficiency of 100% in 24 hours) at 125 μM against S. aureus and 62.5 μM against E. coli. SEM micrographs showed bacterial cells with lower cell density, blebs and other alteration after microcompound treatment.